A STUDY ON ENGLISH STUDENTS DIFFICULTIES IN SPEAKING SKILL - Pricilla, Shania; Dahnilsyah, Dahnilsyah; Masyhur, Masyhur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2024)
Abstract: The purpose of this research is to find out the difficulties faced by thefourth-semester students of English Study Program of Universitas Riau in speakingskill. This research used descriptive quantitative method. In collecting data, theresearcher used a closed questionnaire and 5 point Likert-scale to determine the factorsthat cause students' difficulties in speaking. The survey consists of eight indicators;vocabulary, pronunciation, fluency, grammar, anxiety, shyness, lack of motivation andlack of confidence. The sample of this research was 71 students of fourth-semesterstudents of English Study Program of Universitas Riau. The questionnaire was accessedby the students online via Google Forms. According to the results, Shyness (69.58%) isthe most common speaking difficulty in very difficult criteria, whereas Lack ofMotivation (59.86%) is the least common speaking difficulty in difficult criteria.Key Words: Speaking Skill, Speaking Difficulties, English Students.